Proportion of Pre-dialysis Prolonged QT Dispersion in TwiceWeekly Chronic Hemodialysis Patients and Its Associated Factors - Pattiiha, Arief; Yamin, Muhammad; Lydia, Aida; Abdullah, Murdani (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Cardiovascular disease (CVD) is the common cause of mortality in end-stage renal disease (ESRD) patients undergoing hemodialysis (HD). Causes of CVD in ESRD patients are multifactorial. Ventricular arrhythmia is known as the leading cause of sudden death in dialysis patients. QT dispersion, which is measured from electrocardiography (ECG), is known as one of the parameters to assess the risk of arrhythmia in HD patients. This study aimed to determine the proportion of pre-dialysis prolonged QT dispersion in chronic twice-weekly HD patients and the associated factors. Methods. A cross-sectional study was conducted among HD patients age ≥18 years with dialysis duration of at least three months in Cipto Mangunkusumo Hospital during May–June 2019. Electrocardiography, echocardiography, and blood samples were taken before the dialysis session. Bivariate analysis using Chi-square and Fisher’s exact test was performed on each variable. Significant results were further analysed using logistic regression. Results. A total of 142 subjects were included in this study. The mean age of subjects was 49 (standard deviation (SD) 15) years. Prolonged QT dispersion was found in 51 subjects (35.9%). Multivariate analysis showed prolonged QT dispersion was significantly correlated with systolic dysfunction (PR=1.875 (CI 95% 1.234-2.848); p=0.006) and left ventricle hypertrophy (PR=2.361 (CI 95% 1.032-5.403); p=0.019). Age, diabetes mellitus, hypokalemia, hypomagnesemia, and diastolic dysfunction were not significantly correlated with QT dispersion (p>0.05). Conclusion. The proportion of pre-dialysis prolonged QT dispersion in twice-weekly chronic hemodialysis patients in RSCM is 35.9% and associated with systolic dysfunction and left ventricle hypertrophy